1998
DOI: 10.1016/s0006-3495(98)74024-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Orientation Distributions in Protein Films: III. Yeast Cytochrome c Immobilized on Pyridyl Disulfide-Capped Phospholipid Bilayers

Abstract: Molecular orientation in a hydrated monolayer film of yeast cytochrome c, immobilized via disulfide bonding between Cys-102 and a pyridyl disulfide-capped phospholipid bilayer deposited from an air-water interface onto glass substrates, was investigated. The orientation distribution of the heme groups in the protein film was determined using a combination of absorption linear dichroism, measured in a planarintegrated optical waveguide-attenuated total reflection geometry- and fluorescence anisotropy, measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
44
0
1

Year Published

2003
2003
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 44 publications
2
44
0
1
Order By: Relevance
“…[35,36] In those studies, protein adsorption with conservation of the secondary structure was demonstrated, and methods to elucidate the orientation of the protein or of secondary structural elements were developed. In contrast to the zwitterionic lipid bilayers in those studies, the quartz surface is negatively charged at neutral pH [37] while T4L carries a net positive charge under these conditions. Therefore, the protein-surface interaction is expected to be increased on the quartz surface, and a more severe perturbation of the protein structure is expected.…”
mentioning
confidence: 77%
“…[35,36] In those studies, protein adsorption with conservation of the secondary structure was demonstrated, and methods to elucidate the orientation of the protein or of secondary structural elements were developed. In contrast to the zwitterionic lipid bilayers in those studies, the quartz surface is negatively charged at neutral pH [37] while T4L carries a net positive charge under these conditions. Therefore, the protein-surface interaction is expected to be increased on the quartz surface, and a more severe perturbation of the protein structure is expected.…”
mentioning
confidence: 77%
“…This is mainly due to the foreseen benefits that understanding the kinetics and mechanism of protein adsorption will have essential applications not only in protein analysis, but also on industrial processes, such as the purification and storage of pharmaceutical products, in the biocompatibility of surgical implants, new materials and coatings, in biosensor development as well as in explaining some fundamental biochemical Spectroscopic techniques based on internal total reflection (ITR) in an optical waveguide are one of the most effective methods for investigating molecular-adsorption processes onto surfaces, because they allow in situ measurements without influencing the adsorption process. 2,3 The reported nomenclature in the literature include slab optical waveguide (SOWG) spectroscopy, 4-17 the integrated optical waveguideattenuated total reflection technique (IOW-ATR) [18][19][20][21][22][23][24][25][26][27] and optical waveguide lightmode spectroscopy (OWLS). 1,[28][29][30][31][32][33][34][35][36][37][38] These techniques have been successfully used in real-time studies on the adsorption of dye molecules 11,12,[14][15][16] and proteins 4,8,[18][19][20][21][22][23][24][25][28]…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The reported nomenclature in the literature include slab optical waveguide (SOWG) spectroscopy, 4-17 the integrated optical waveguideattenuated total reflection technique (IOW-ATR) [18][19][20][21][22][23][24][25][26][27] and optical waveguide lightmode spectroscopy (OWLS). 1,[28][29][30][31][32][33][34][35][36][37][38] These techniques have been successfully used in real-time studies on the adsorption of dye molecules 11,12,[14][15][16] and proteins 4,8,[18][19][20][21][22][23][24][25][28][29][30][31][32][33][34][35][36][37]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35,36] Dabei wurde gezeigt, dass die Sekundärstruktur von T4L bei Adsorption auf einer Doppelschicht eines zwitterionischen Lipids erhalten bleibt, und es wurden Methoden zur Bestimmung der Orientierung adsorbierter Proteine entwickelt. Im Unterschied zu den dort verwendeten Lipiddoppelschichten ist die in dieser Untersuchung betrachtete Quarzoberfläche bei neutralem pHWert [37] negativ geladen, während T4L positiv geladen ist. Daher sollte die Wechselwirkung zwischen Protein und Oberfläche bei der Adsorption auf einer Quarzoberfläche stärker sein als auf einer Lipiddoppelschicht; daher wird auch eine stärkere Veränderung der Proteinstruktur erwartet.…”
unclassified